2020
DOI: 10.1001/jamainternmed.2020.0664
|View full text |Cite
|
Sign up to set email alerts
|

Severe Lung Injury Associated With Use of e-Cigarette, or Vaping, Products—California, 2019

Abstract: more than 2700 patients have been hospitalized with e-cigarette, or vaping, product use-associated lung injury (EVALI) across the United States. This report describes the outbreak in California, a state with one of the highest case counts and with a legal adult-use (recreational) cannabis market. OBJECTIVE To present clinical characteristics and vaping product exposures of patients with EVALI in California. DESIGN, SETTING, AND PARTICIPANTS Case series describing epidemiologic and laboratory data from 160 hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 23 publications
1
48
0
Order By: Relevance
“…In the series by Blagev et al, 12 33 of 60 patients (55%) were admitted to an ICU, and 19 patients (32%) underwent bronchoscopy. More recent additions to the literature, including those by Zou et al, 20 Henzerling et al, 14 and MacMurdo et al, 16 demonstrated similar ICU admission rates (range, 46%-47%) and bronchoscopy rates (range, 19%-47%). By comparison, only 8 (26%) of our patients were treated in an ICU, and a much larger proportion of all patients (22 [77%]) underwent bronchoscopy.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…In the series by Blagev et al, 12 33 of 60 patients (55%) were admitted to an ICU, and 19 patients (32%) underwent bronchoscopy. More recent additions to the literature, including those by Zou et al, 20 Henzerling et al, 14 and MacMurdo et al, 16 demonstrated similar ICU admission rates (range, 46%-47%) and bronchoscopy rates (range, 19%-47%). By comparison, only 8 (26%) of our patients were treated in an ICU, and a much larger proportion of all patients (22 [77%]) underwent bronchoscopy.…”
Section: Discussionmentioning
confidence: 84%
“…All patients survived, and 20 patients (65%) were seen in follow-up. Median (IQR) time to follow-up after hospital discharge was 16 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)…”
Section: Follow-upmentioning
confidence: 99%
See 1 more Smart Citation
“…An outbreak of e-cigarette or vaping product use associated lung injury (EVALI) in 2019–20 resulted in hospital admissions and deaths. Vitamin E acetate (VEA) inside tetrahydrocannabinol (THC) vaping devices was identified as the most likely indicator of injury [ 1 , 2 ]. Acute lung injury has been reported in EVALI lung biopsies and autopsies [ 3 , 4 ], and it has been hypothesized that VEA may have chemically reacted to create toxic ketene (ethenone) in the presence of high temperatures [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…California identified 210 EVALI cases hospitalized during June 18, 2019-February 23, 2020, † and 65 of 87 (75%) interviewed patients reported using THC vaping products obtained from informal sources (1) * California has suspended use of the probable case definition, in which the patient has infection identified via culture or PCR but clinical team caring for patient believes this is not the sole cause of the underlying respiratory disease process; or patient has no evidence of pulmonary infection, but minimum criteria to rule out pulmonary infection not met (testing not performed). † Includes using an electronic device (e.g., electronic nicotine delivery system [ENDS], electronic cigarette, e-cigarette, vaporizer, vape(s), vape pen, dab pen, or other) or dabbing to inhale substances (e.g., nicotine, marijuana, tetrahydrocannabinol (THC), THC concentrates, cannabidiol, synthetic cannabinoids, flavorings, or other substances).…”
mentioning
confidence: 99%